A comprehensive analysis of the causal factors in repair, maintenance, alteration, and addition works: A novel hybrid fuzzy-based approach. (1st December 2022) - Mohandes, Saeed Reza; Karasan, Ali; Erdoğan, Melike; Ghasemi Poor Sabet, Pejman; Mahdiyar, Amir; Zayed, Tarek
Highlights: Critical causes of RMAA-related accidents are identified. Novel hybrid fuzzy-based algorithms are employed for result accuracy enhancement. Considerable inherent interrelationships exist among RMAA-related causal factors. "Limited financial/safety resources of SMEs" is the most influential causal factor. The identified causes are prioritized using IVIF-DEMATEL-ANP method. Abstract: Despite the recent improvements made to the area of occupational health and safety (OHS) within the construction sector, the Repair, Maintenance, Minor alteration, and Addition (RMAA) works have been given scant attention. In this study, given the significance of the injuries reported in the RMAA sector, a meticulous investigation is conducted into the causal factors contributing to the related accidents by capturing their causal interrelationships together with their importance levels. To this end, first, a comprehensive list of factors contributing to RMAA accidents was obtained through an extensive literature review and experts' interviews. Then, through the lenses of qualified relevant experts in Hong Kong, the proposed interval-valued intuitionistic fuzzy (IVIF) DEMATEL and IVIF analytic network process were employed to respectively uncover the cause-and-effect relationships among these factors and prioritize them. The findings show that "the lack of assessment and praising of workers' OHS understanding and performance, " "the high turnover rate of workers resulting in difficulties in providing safety training and education, " and "lack of safety training for workers" are the most critical causes to be given full attention by construction safety managers. The methodological approach proposed in this study brings about two theoretical contributions: unraveling interrelationships existing among the causal factors, and prioritization of them considering their interrelationships. The findings reported in this study also aid decision-makers in improving the critical causal factors in a way to enhance the OHS of RMAA sector.